Evaluation of Seismotectonic And Seismicity in Buin Zahra area With an Emphasis on Buin Zahra City (Revista Geoaraguaia, 2021)
In this paper, we study the seismotectonic and seismicity status of the Buin Zahra region, in Qazvin province. The studied area has experienced two catastrophic earthquakes in 1962 and 2002 such that more than 12,450 people were killed and about 4,280 people were injured. However, the exact status of human and financial injuries of historical earthquakes is not clear and only the occurrence of earthquakes is confirmed by the ruins and archaeological studies in this area. The emphasis of this work is on the city of Buin Zahra because it is the center of the considered area. In this work, geological and quaternary geological status, seismotectonic, and seismicity of the region are investigated. In this study, geological maps and reports, satellite images, and other researches were used to assess seismic sources, faults. Regarding the seismicity history of the study area, various scientific sources reporting the characteristics of earthquakes were utilized considering the occurrence of numerous earthquakes and the geological and seismological importance of the region. To obtain seismic parameters, common methods such as the Kijko-Slevolle were employed. the results showed that this region, with multiple active faults and a history of various earthquakes, is highly seismically active such that there is the probability of earthquakes with magnitudes of 5-6 and even more than 7 in certain periods.